Seismic Attributes Aided Characterization of Margin Backstepping and Advance along Isolated Carbonate Sequences, Sirt Basin, Libya - Abdalla, Muneer A. (Al-Mukhtar Journal of Sciences, 2021)
Isolated carbonate platforms are common and contain significant hydrocarbon accumulations, particularly in the tectonically complex Sirt Basin in Libya. This study investigates the margin cyclicity of two carbonate stratigraphic sequences developed on an isolated carbonate platform in the NW Sirt Basin using 3-D post-stack seismic volume and wireline log data. The two sequences (sequences 4 and 5) are bounded by unconformity surfaces from the base and top. Seismic attributes show that each sequence displays a cycle of margin backstepping followed by margin advance for several hundred meters. This study concludes that the margin backstepping and advance are mainly influenced by sea-level changes. A rapid sea-level rise caused the backstepping, whereas slow sea-level rise caused the margin advance.